Psychopathology and Associated Risk Factors Among Forcibly Displaced Syrian Children and Adolescents - (:unkn) unknown (SPRINGER, 2018)
More than half of the 2.7 million registered Syrian refugees in Turkey are under 18 years of age. This study investigates prevalence of psychopathology and associated risk factors in refugee children in Turkey. Of a total of 218 children aged 9-15 years, 56.2% lost someone important to them, 55.1% saw dead or wounded people, 70.4% witnessed explosions or gun battles, 42.5% witnessed people being tortured and 25.6% personally experienced cruelty/torture during war. Prevalence of PTSD was 18.3% and that of anxiety-related disorders were as high as 69.0%. Death of an important person (p = .032) and male gender (p = .040) were associated with PTSD; whilst exposure to cruelty or torture (p = .014) and increasing duration of refuge (p = .042) were significantly associated with development of anxiety disorders. Findings of the present study reveals existence of the expected but unspoken mental health needs among the Syrian children in Turkey.
Keywords: Refugee children; Mental health; Trauma; Anxiety; PTSD; Turkey; POSTTRAUMATIC-STRESS-DISORDER; MENTAL-HEALTH; DIFFICULTIES QUESTIONNAIRE; ACCULTURATIVE STRESS; TRAUMATIC EVENTS; REFUGEE CHILDREN; WAR EXPERIENCES; STRENGTHS; SYMPTOMS; CONFLICT